PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Suhartini, Dwi; Megasyara, Ira (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2018)
This research aims to test the influence of corporate social responsibility (CSR) against the company's value and profitability, as well as how the influence of corporate social responsibility disclosures of the company's profitability as an intervening variable. There are about 70% Indonesia environmental damage caused by mining operations that implement CSR programs and mining companies can reduce the environmental impact of such business. This research uses a quantitative approach to the analysisof data by the method of partial least square (PLS). Population as many as six company the mining sector listed on the effect indonesia of 2012-2016 .A method of the sample collection use purpose of sampling , as many as 30 report a finance company. This research result indicates that csr not contributing to value of enterprise, but contribute to profitability. Profitability capable of being variable intervening between relations csr on the company, it means profitability high giving effect to the high value of enterprise.